Spectral analysis of granular material reaction to long-term weak dynamic effect; IOP Conference Series: Materials Science and Engineering; Vol. 91: VI International Scientific Practical Conference on Innovative Technologies and Economics in Engineering, Yurga, Russia, 21-23 May 2015 - Kazantsev A. A. Anton Aleksandrovich (Advanced technologies and equipment for agro-industrial complex (AIC) and mining, 2015)
Title screen